Relationship between the Y Balance Test scores and soft tissue injury incidence in a soccer team - Gonell, A. C.; Romero, J. A. P.; Soler, L. M. (The International Journal of Sports Physical Therapy, 2015)
Background: Although the dynamic balance has been proposed as a risk factor for sports-related injuries, few researchers have used the Y balance test to examine this relationship. The purpose of this study was to determine if the Y Balance Test (YBT) is a valid test for determining subjects susceptible to soft tissue injury among soccer players on a professional team. Study Design: Prospective cohort Methods and Measures: Prior to the 2011 football (soccer) season, the anterior, posteromedial and postero- lateral YBT reach distances and limb lengths of 74 soccer players were measured. Athletes` physiothera- pists documented how many days the players were unable to play due to the injuries. After normalizing for lower limb length, each of the reach distances, right/left reach distance difference and composite reach distance were examined using odds ratios and logistic regression analysis. Results: Logistic regression models indicated that players with a difference of equal or greater than 4cm between lower limbs in posteromedial direction were 3.86 more likely to sustain a lower extremity injury (p=0.001). Results indicate that players who had lower scores than the mean in each reach direction, inde- pendently, were almost two times more likely to sustain an injury. Conclusions: The results suggest that YBT can be incorporated into physical examinations to identify soccer players who are susceptible to risk of injury.